2012
DOI: 10.1177/230949901202000321
|View full text |Cite
|
Sign up to set email alerts
|

Total Wrist Arthroplasty Using the Universal 2 Prosthesis

Abstract: purpose. To report outcomes of 21 total wrist arthroplasties (TWA) using the Universal 2 prosthesis. Methods. Five men and 14 women aged 44 to 82 (mean, 62) years underwent 21 total wrist arthroplasties for rheumatoid arthritis (n=19) and post-traumatic arthritis (n=2) by a single surgeon using the Universal 2 prosthesis. Pre-and post-operative pain and function were assessed by a single surgeon using the Disabilities of the Arm, Shoulder and Hand (DASH) score and the patient-rated wrist evaluation (PRWE) scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 24 publications
2
58
1
1
Order By: Relevance
“…14 of the studies reported pain relief, 6,[8][9][10][11][12][13]15,17,[19][20][21][22][23] but only 8 used validated scales, and the rest used ordinal scales, severity, and/or frequency to measure pain. Using the visual analogue scale (VAS) for pain, 2 studies reported improvement in the mean score from 8 to 2 (p<0.05) 9 and from 67 to 27 (p<0.001), 23 but one study reported no significant improvement.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…14 of the studies reported pain relief, 6,[8][9][10][11][12][13]15,17,[19][20][21][22][23] but only 8 used validated scales, and the rest used ordinal scales, severity, and/or frequency to measure pain. Using the visual analogue scale (VAS) for pain, 2 studies reported improvement in the mean score from 8 to 2 (p<0.05) 9 and from 67 to 27 (p<0.001), 23 but one study reported no significant improvement.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Using the patient-rated wrist evaluation (PRWE) questionnaire, one study reported improvement in the mean pain scores from 43.0 to 18.2 (p<0.001), 12 and another reported just a mean postoperative score of 11 (standard deviation, 10). 13 One study used the pain component of the Hospital for Special Surgery system and reported a mean postoperative score of 0.4 out of 10.…”
mentioning
confidence: 99%
See 3 more Smart Citations